Metabolomic Identification of a Novel Pathway of Blood Pressure Regulation Involving Hexadecanedioate. Issue 2 (August 2015) - Menni, Cristina; Graham, Delyth; Kastenmüller, Gabi; Alharbi, Nora H.J.; Alsanosi, Safaa Md; McBride, Martin; Mangino, Massimo; Titcombe, Philip; Shin, So-Youn; Psatha, Maria; Geisendorfer, Thomas; Huber, Anja; et al.
Abstract : High blood pressure is a major contributor to the global burden of disease and discovering novel causal pathways of blood pressure regulation has been challenging. We tested blood pressure associations with 280 fasting blood metabolites in 3980 TwinsUK females. Survival analysis for all-cause mortality was performed on significant independent metabolites ( P <8.9×10 −5 ). Replication was conducted in 2 independent cohorts KORA (n=1494) and Hertfordshire (n=1515). Three independent animal experiments were performed to establish causality: (1) blood pressure change after increasing circulating metabolite levels in Wistar–Kyoto rats; (2) circulating metabolite change after salt-induced blood pressure elevation in spontaneously hypertensive stroke-prone rats; and (3) mesenteric artery response to noradrenaline and carbachol in metabolite treated and control rats. Of the15 metabolites that showed an independent significant association with blood pressure, only hexadecanedioate, a dicarboxylic acid, showed concordant association with blood pressure (systolic BP: β [95% confidence interval], 1.31 [0.83–1.78], P =6.81×10 −8 ; diastolic BP: 0.81 [0.5–1.11], P =2.96×10 −7 ) and mortality (hazard ratio [95% confidence interval], 1.49 [1.08–2.05]; P =0.02) in TwinsUK. The blood pressure association was replicated in KORA and Hertfordshire. In the animal experiments, we showed that oral hexadecanedioate increased both circulating hexadecanedioate and blood pressure in Wistar–Kyoto rats, whereas blood pressure elevation with oral sodium chloride in hypertensive rats did not affect hexadecanedioate levels. Vascular reactivity to noradrenaline was significantly increased in mesenteric resistance arteries from hexadecanedioate-treated rats compared with controls, indicated by the shift to the left of the concentration–response curve ( P =0.013). Relaxation to carbachol did not show any difference. Our findings indicate that hexadecanedioate is causally associated with blood pressure regulation through a novel pathway that merits further investigation. Abstract : Supplemental Digital Content is available in the text.